An Exploratory Econometric Analysis of Shared Electronic Banking Network Adoption - KAUFFMAN, Robert J. (Institutional Knowledge at Singapore Management University, 1994)
This paper focuses on a specific kind of interorganizational system — shared electronic banking networks — and identifies firm characteristics that are likely to influence the perceived business value of network membership and thus lead to early adoption. We undertake an exploratory econometric analysis of the adoption of Yankee 24, a large shared electronic banking network in the northeastern USA. Using Bass's analytical diffusion model, we categorize Yankee 24 members into earlier and later adopters. Probit models are estimated to assess the impact of explanatory variables on network adoption. We find that a bank's total demand deposits have a positive impact on early adoption, while the number of a bank's branch offices, a proxy for the size of its proprietary network, has a negative impact on early adoption.